Low-emission and energetically efficient co-gasification of coal by incorporating plastic waste: A modeling study. (July 2022) - Hasanzadeh, Rezgar; Mojaver, Parisa; Azdast, Taher; Chitsaz, Ata; Park, Chul B.
Abstract: The issues of global plastic waste generation and demand for hydrogen energy can be simultaneously resolved by gasification process. In this regard, feasibility and efficiency of steam and air co-gasification of coal by incorporating five different and prevalent types of plastic waste were investigated in this modeling study. All steam and air coal/plastic waste co-gasification types were multi-objective optimized utilizing a response surface methodology. The best co-gasification types were selected using VIekriterijumsko KOmpromisno Rangiranje (VIKOR) analysis. Overall, the results showed that incorporating plastic waste into coal gasification improved hydrogen concentration in the syngas and increased normalized carbon dioxide production due to the high carbon content of plastic waste and activation of water-gas and CO shift reactions. VIKOR analysis revealed that steam coal/low density polyethylene was the best optimized co-gasification type with hydrogen concentration of 62.8 mol %, normalized carbon dioxide production of 2.60 g/mol, based on the feedstock entering the system, and energy efficiency of 76.6%. Increasing gasifier temperature enhanced hydrogen concentration and decreased normalized carbon dioxide production. The energy efficiency was markedly improved by increasing the moisture content and decreasing the ratio of steam/feedstock. This study confirmed the hypothesis of efficient utilization of plastic waste in coal/plastic waste co-gasification. Graphical abstract: Image 1 Highlights: Steam and air co-gasification of coal by incorporating prevalent plastic waste type. Co-gasification multi-objective optimization utilizing response surface methodology. Multi-criteria decision analysis using VIKOR technique. Energetically efficient co-gasification with 76.6% energy efficiency. Low-emission co-gasification with 2.60 g/mol normalized carbon dioxide emission.